Multi-Omics Approach in Amelioration of Food Products - Dutta, Bandita; Lahiri, Dibyajit; Nag, Moupriya; Abukhader, Rose; Sarkar, Tanmay; Pati, Siddhartha; Upadhye, Vijay; Pandit, Soumya; Amin, Mohamad Faiz Mohd; Al Tawaha, Abdel Rahman Mohammad Said; Kumar, Manoj; Ray, Rina Rani (Frontiers in Microbiology, 2022)
Determination of the quality of food products are essential key factors needed for safe-guarding the quality of food for the interest of the consumers. Along with the nutritional and sensory improvements are necessary for delivering better quality products. The implementation of multi-omics approach has been important for over-all enhancement in the quality of the food. This review uses various recent technologies like proteomics, transcriptomics and metabolomics for overall enhancement in the quality of the food products. The matrix associated with the food products require the use of sophisticated technologies that help in the extraction of large amount of information necessary for the amelioration of the food products. This review would provide a wholesome view of how various recent technologies that can be used for better quality food products and enhancing the shelf-life.